Poly‐ADP‐ribosyl polymerase‐14 promotes T helper 17 and follicular T helper development. Issue 4 (28th September 2015) - Mehrotra, Purvi; Krishnamurthy, Purna; Sun, Jie; Goenka, Shreevrat; Kaplan, Mark H.
Summary: Transcription factors are critical determinants of T helper cell fate and require a variety of co‐factors to activate gene expression. We previously identified the ADP ribosyl‐transferase poly‐ADP‐ribosyl polymerase 14 (PARP‐14) as a co‐factor of signal transducer and activator of transcription (STAT) 6 that is important in B‐cell and T‐cell responses to interleukin‐4, particularly in the differentiation of T helper type 2 (Th2) cells. However, whether PARP‐14 functions during the development of other T helper subsets is not known. In this report we demonstrate that PARP‐14 is highly expressed in Th17 cells, and that PARP‐14 deficiency and pharmacological blockade of PARP activity result in diminished Th17 differentiation in vitro and in a model of allergic airway inflammation. We further show that PARP‐14 is expressed in T follicular helper (Tfh) cells and Tfh cell development is impaired in PARP‐14‐deficient mice following immunization with sheep red blood cells or inactivated influenza virus. Decreases in Th17 and Tfh development are correlated with diminished phospho‐STAT3 and decreased expression of the interleukin‐6 receptor α ‐chain in T cells. Together, these studies demonstrate that PARP‐14 regulates multiple cytokine responses during inflammatory immunity.